The use of co-production, co-design and co-creation to mobilise knowledge in the management of health conditions: a systematic review - Grindell, Cheryl; Coates, Elizabeth; Croot, Liz; O’Cathain, Alicia (BMC health services research, 2022)
Background Knowledge mobilisation is a term used in healthcare research to describe the process of generating, sharing and using evidence. ‘Co’approaches, such as co-production, co-design and co-creation, have been proposed as a way of overcoming the knowledge to practice gap. There is a need to understand why researchers choose to adopt these approaches, how they achieve knowledge mobilisation in the management of health conditions, and the extent to which knowledge mobilisation is accomplished. Methods Studies that explicitly used the terms co-production, co-design or co-creation to mobilise knowledge in the management of health conditions were included. Web of Science, EMBASE via OvidSP, MEDLINE via OvidSP and CINHAL via EBSCO databases were searched up to April 2021. Quality assessment was carried out using the Joanna Briggs Institute qualitative quality assessment checklist. Pluye and Hong’s seven steps for mixed studies reviews were followed. Data were synthesised using thematic synthesis. Results Twenty four international studies were included. These were qualitative studies, case studies and study protocols. Key aspects of ‘co’approaches were bringing people together as active and equal partners, valuing all types of knowledge, using creative approaches to understand and solve problems, and using iterative prototyping techniques. Authors articulated mechanisms of action that included developing a shared understanding, identifying and meeting needs, giving everyone a voice and sense of ownership, and creating trust and confidence. They believed these mechanisms could produce interventions that were relevant and acceptable to stakeholders, more useable and more likely to be implemented in healthcare. Varied activities were used to promote these mechanisms such as interviews and creative workshops. There appeared to be a lack of robust evaluation of the interventions produced so little evidence in this review that ‘co’approaches improved the management of health conditions. Conclusion Those using ‘co’approaches believed that they could achieve knowledge mobilisation through a number of mechanisms, but there was no evidence that these led to improved health. The framework of key aspects and mechanisms of ‘co’approaches developed here may help researchers to meet the principles of these approaches. There is a need for robust evaluation to identify whether ‘co’approaches produce improved health outcomes. Trial Registration PROSPERO CRD42020187463 .